2020
DOI: 10.1002/ccr3.3161
|View full text |Cite
|
Sign up to set email alerts
|

Persistent hypoglycemia due to an IGF‐II‐secreting malignant pheochromocytoma: a case report and literature review

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…The authors of first report described a fatal case of pheochromocytoma that presented with intractable hypoglycemia with elevated levels of IGF-2 as the most likely cause of hypoglycemia. 20 In the second report, the authors proposed that direct tumor consumption was the cause of hypoglycemia based on F-2-fluorodeoxy-D- glucose positron emission tomography imaging of the tumor. 18 The authors of the third report suggested that direct eutopic islet cell response to the pheochromocytoma with high and inappropriate levels of insulin was the underlying cause of the hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…The authors of first report described a fatal case of pheochromocytoma that presented with intractable hypoglycemia with elevated levels of IGF-2 as the most likely cause of hypoglycemia. 20 In the second report, the authors proposed that direct tumor consumption was the cause of hypoglycemia based on F-2-fluorodeoxy-D- glucose positron emission tomography imaging of the tumor. 18 The authors of the third report suggested that direct eutopic islet cell response to the pheochromocytoma with high and inappropriate levels of insulin was the underlying cause of the hypoglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Direct glucose consumption by the tumor in the presence of an elevated burden of disease, according to the results of the 18F-FDG-PET/CT scan findings. This was reported in a few case reports, with the presence of FDG uptake predominantly in the tumor mass, and the reduction in the normal FDG uptake throughout the rest of the body, most prominently in the brain [ 37 , 38 ];…”
Section: Pathophysiological Mechanisms Of Hypoglycemia Related To Met...mentioning
confidence: 93%
“…The principal mechanisms proposed are subsequently: Direct glucose consumption by the tumor in the presence of an elevated burden of disease, according to the results of the 18F-FDG-PET/CT scan findings. This was reported in a few case reports, with the presence of FDG uptake predominantly in the tumor mass, and the reduction in the normal FDG uptake throughout the rest of the body, most prominently in the brain [ 37 , 38 ]; Excessive ectopic cancer production of aberrant IGF-II or pro-IGF-II, that are less protein-bound and subsequently more bioactive than normal IGF-II. Multiple actions of these compounds can be responsible for the development of hypoglycemia, primarily in the reduction of glucose hepatic output, by decreasing hepatic gluconeogenesis and glycogenolysis.…”
Section: Pathophysiological Mechanisms Of Hypoglycemia Related To Met...mentioning
confidence: 99%
See 1 more Smart Citation